Probing bottom-associated production of a TeV scale scalar decaying to a top quark and dark matter at the LHC - Amandeep Kaur Kalsi; Teruki Kamon; Seulgi Kim; Jason S. H. Lee; Denis Rathjens; Youn Jung Roh; Adrian Thompson; Ian James Watson (Journal of High Energy Physics)
Abstract A minimal non-thermal dark matter model that can explain both the existence of dark matter and the baryon asymmetry in the universe is studied. It requires two color-triplet, iso-singlet scalars with O TeV $$ \mathcal{O}\left(TeV\right) $$ masses and a singlet Majorana fermion with a mass of O GeV $$ \mathcal{O}\left(GeV\right) $$ . The fermion becomes stable and can play the role of the dark matter candidate. We consider the fermion to interact with a top quark via the exchange of QCD-charged scalar fields coupled dominantly to third generation fermions. The signature of a single top quark production associated with a bottom quark and large missing transverse momentum opens up the possibility to search for this type of model at the LHC in a way complementary to existing monotop searches.